Glycomethanethiosulfonates: powerful reagents for protein glycosylation - Davis, B; Maughan, M; Green, M; Ullman, A; Jones, J (2000)
Twelve novel glycomethanethiosulfonate (glyco-MTS) protein glycosylation reagents have been prepared. Their use in a controlled site-selective glycosylation strategy that combines site-directed mutagenesis with chemical modification allows protein glycosylation with concomitant control of (i) site, (ii) carbohydrate, (iii) anomeric stereochemistry, (iv) sugar to protein spacer arm nature and (v) degree of glycan protection. The ability of these highly selective and yet reactive reagents has been illustrated by the introduction of D-glucosyl and N-Ac-D-glucosaminyl residues to both external and hindered internal sites in a model protein - the serine protease enzyme subtilisin Bacillus lentus (SBL) - using corresponding gluco-MTS 1 and N-Ac-glucosamine-MTS 2. Molecular modelling studies provide a rationale for the strikingly different effects of these reagents on the properties of the protein despite differing only in the nature of their C-2 substituents. Copyright (C) 2000 Elsevier Science Ltd.